Energy Poverty, Practice, and Policy - Butler, Catherine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
(3z(BCatherine Butler$1 (Bs new book is theoretically innovative, bringing much-needed insights on poverty and vulnerability into the study of Social Practices. It offers in-depth analysis of how (3z(Binvisible energy policies(3y (Boperate in the real world, revealing the important intersections between welfare policies and energy in everyday life. Amid the cost of living crisis, and the ever-more contested politics of social security, this book makes a hugely timely contribution, and will be a valuable resource for researchers, students, and all those concerned with understanding and promoting energy justice.(3y $1 (BSarah Royston, Anglia Ruskin University, UK This Open Access book examines the implications of welfare policy for energy poverty and engages with key conceptual debates at the forefront of energy demand research. Academic work on energy poverty has rarely been brought into conversation with practice-theory-based approaches to energy use and sustainability. This book reveals how novel insights can be made visible through combining these different ways of thinking about energy demand issues. It presents a distinctive approach to energy poverty that places inequalities at the heart of debates about the advancing energy intensity of contemporary societies. Dr Catherine Butler is Senior Lecturer in Human Geography at University of Exeter. Her research centres around analysis of environmental governance processes with focus on the intersections between policy, politics, and everyday life. She has published extensively on topics including energy transitions in everyday life, behavioural change and social practice, wellbeing impacts of environmental change processes, and governance of climate adaptation. This book arises out of her four-year EPSRC (Engineering and Physical Sciences Research Council) funded project. .s
CHAPTER 1: Introduction -- CHAPTER 2: Poverty and Energy -- CHAPTER 3: Practice and Energy -- CHAPTER 4: Policy: Energy Demand and Welfare in the UK -- CHAPTER 5: Invisible Energy Policy and Energy Capabilities -- CHAPTER 6: Energy, Poverty, Practice, and Inequality -- CHAPTER 7: Conclusions: Reconceptualising Energy Poverty and Practice. .
Keywords: Environmental sciences -- Social aspects; Energy policy; Energy and state; Environmental policy; Human ecology -- Study and teaching; Environmental geography; Environmental Social Sciences; Energy Policy, Economics and Management; Environmental Policy; Environmental Studies; Integrated Geography